Pengaruh Pemberian Baby Massage Lavender Essential Oil terhadap Peningkatan Kualitas Tidur pada Bayi Usia 3-12 Bulan - Dita Puji Kusuma; Kamidah Kamidah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background : poor sleep quality in babies will result in decreased immunity, impaired growth and physical development, and have an impact on the growth and development of the baby's brain. 1 year of age is a golden period for brain development. Baby Massage is a type of stimulation that will stimulate the development of the structure and function of cells in the brain. The improvement in the quality of baby's sleep during baby massage is due to an increase in the levels of serotonin secretion produced during massage. Apart from the Baby Massage method, adding Lavender Essential Oil also has an effect on improving the quality of baby's sleep because essential oil can influence brain function activities through the nervous system which is related to the sense of smell. Lavender contains esters which can calm and have a direct effect on the nervous system. Objective: to determine the effect of giving Baby Massage lavender essential oil on improving the sleep quality of babies aged 3-12. Method: Pre-Experiment with One Group Pretest Posttest design. Sample of 30 respondents. Respondents were given a massage once and then evaluated after 24 hours. Data analysis used the Wilcoxon test. Results: The quality of sleep before being given Baby Massage Lavender Essential was that all 30 respondents had poor sleep quality. The majority of sleep quality after being given Baby Massage Lavender Essential was good, namely 27 respondents (90%). The statistical test obtained a p-value of 0.000, <0.05. Conclusion: There is an effect of giving Baby Massage lavender essential oil on improving the sleep quality of babies aged 3-12.